Populational Model of Rhipicephalus microplus in Beef Cattle in the Southern Region of Paraná, Brazil - Daniel Perotto; Nilceu Lemos da Silva; Meiby Carneiro de Paula Leite; Carolina Fregonesi de Souza; Julio Cesar de Souza (Veterinary Sciences)
In order to describe the population dynamics of R. microplus in the southern region of the state of Paraná, Brazil, and to identify racial differences between hosts in the level of infestation by this parasite, the teleogins of approximately 70 males per year were counted every 14 days for 5 years. The herd comprised eight genetic groups, aged 12 to 24 months, in an area of 76 ha (60 ha of native fields and 16 ha of Hemarthria altíssima). The monthly averages of the counts per animal were analyzed using the GENMOD procedure, which accounts for the effects of genetic group, month, genetic group × month and cycle. Three generations of ticks of increasing infestation intensity were analyzed in December, February and May, respectively. Animals from Caracu and Canchim breeds as well as Charolais × Caracu and Aberdden Angus × Canchim cross-breeds had the lowest levels of infestation compared to Charolais and Aberdeen Angus. We conclude that by employing the aforementioned mixed breeds, in combination with a strategic control of initiating the application of acaricides in November, followed by two to three treatments every 21 days, this procedure represents the most effective method of controlling ticks in this region.